Relationships between body length and bony structure measures in North American temperate freshwater fishes - Kamden C. Glade; Jay Holland; Baylor Short; Kendra Fink; Andrew W. Hafs (Journal of Fish Biology, 2025)
Stomach content investigations of piscivorous fishes provide resource managers with valuable information concerning diet patterns, community structure and species interactions. Unique bony structures are often used to identify partially digested prey fish, and recent advancements in molecular techniques have provided increased taxonomic resolution of prey fish remains. However, gravimetric and volumetric methods only account for the partial remains recovered in the sample, which could lead to underestimates of the dietary contributions of digested prey items identified using these techniques. We therefore investigated relationships between total length and bony structures for multiple fish taxa observed in the diets of piscivorous fishes in Minnesota lakes using linear regressions. Cleithra, otoliths, backbone measurements, average vertebrae lengths and ictalurid pectoral spine lengths were used to create equations to estimate total length of digested prey. Predictive equations were developed for families, genera and species, as well as general equations averaged across all taxa. Nearly all equations were statistically significant ( p r 2 ≥ 0.85), although there was substantial variability among taxa and structures. These equations will give investigators an additional tool to maximize the information gained from fish diet studies.